2017
DOI: 10.1021/acsami.6b14000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alignment and Electronic Structure of N,N′-Dibutyl-3,4,9,10-perylene-tetracarboxylic-diimide Molecules on MoS2 Surfaces

Abstract: The molecular orientation of organic semiconductors on a solid surface could be an indispensable factor to determine the electrical performance of organic-based devices. Despite its fundamental prominence, a clear description of the emergent two-dimensional layered material-organic interface is not fully understood yet. In this study, we reveal the molecular alignment and electronic structure of thermally deposited N,N'-dibutyl-3,4,9,10-perylene-dicarboximide (PTCDI-C4) molecules on natural molybdenum disulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Polarized Raman spectroscopy can provide qualitative information about molecular orientation, , and more quantitative information can be extracted with some knowledge of the molecular Raman tensor using azimuthally and radially polarized light . Film structure can also be characterized by X-ray techniques such as diffraction, grazing-incidence wide-angle X-ray scattering (GIWAXS), and near-edge X-ray absorption fine structure (NEXAFS), , or by scanning probe techniques such as scanning tunneling microscopy (STM) or atomic force microscopy . Many of these tools also provide complementary information about the electronic structure of the heterojunction and thus should be used in combination to more fully elucidate the links between the physical structure of thin films and the electronic properties of the constituent materials.…”
mentioning
confidence: 99%
“…Polarized Raman spectroscopy can provide qualitative information about molecular orientation, , and more quantitative information can be extracted with some knowledge of the molecular Raman tensor using azimuthally and radially polarized light . Film structure can also be characterized by X-ray techniques such as diffraction, grazing-incidence wide-angle X-ray scattering (GIWAXS), and near-edge X-ray absorption fine structure (NEXAFS), , or by scanning probe techniques such as scanning tunneling microscopy (STM) or atomic force microscopy . Many of these tools also provide complementary information about the electronic structure of the heterojunction and thus should be used in combination to more fully elucidate the links between the physical structure of thin films and the electronic properties of the constituent materials.…”
mentioning
confidence: 99%
“…It is generally observed that the molecules with a longer alkyl chain preferentially grow with an end-on orientation. In PTCDI derivatives, R = C 4 H 9 (C4) or longer may have an end-on orientation on any substrate. , The C1 molecule is an intermediate case that has a face-on orientation on graphene (or HOPG) and a mixture of face-on and end-on orientations on SiO 2 . It is interesting to note that the surfaces of C0 and C1 do not correlate with the molecular boundary in the crystal structures (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50][51] CTEs have also been identified in numerous TMDC heterojunctions with small molecules. [52][53][54] In organic donor/acceptor heterojunctions, CTEs have been observed in sensitive sub-bandgap absorption and photoluminescence measurements, along with some evidence of very small photocurrents in quantum efficiency measurements of photovoltaic devices. 55 While some CTEs may dissociate into free carriers, a number of analyses suggest that such CTEs can inhibit free charge generation and reduce the voltage of OPVs.…”
Section: Discussionmentioning
confidence: 99%